2002
DOI: 10.1001/archotol.128.12.1396
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase π Expression in Nasopharyngeal Cancer

Abstract: Nasopharyngeal tumor cells may respond to pro-oxidant conditions by modulating intracellular antioxidant defense. Glutathione S-transferase pi expression appears to be associated with lymphogenous metastasis in NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…GSTP1 is a significant downstream molecule in the EGFR signaling network, and EGFR-regulated phosphorylated GSTP1 is responsible for chemo resistance in NPC cells [44,46]. Further studies found that GSTP1 was also associated with lymphogenous metastasis in NPC [47], and this may lead to poor prognosis. Next, we focus on radiation-resistant NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…GSTP1 is a significant downstream molecule in the EGFR signaling network, and EGFR-regulated phosphorylated GSTP1 is responsible for chemo resistance in NPC cells [44,46]. Further studies found that GSTP1 was also associated with lymphogenous metastasis in NPC [47], and this may lead to poor prognosis. Next, we focus on radiation-resistant NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chen reported that 58% (83/143) primary NPC, 69.8% (30/43) recurrent NPC, and 65% (13/20) metastatic NPC tissues highly expressed GSTP1 [29]. Jayasurya reported that all 55 NPC tissues showed positive GSTP1 immunoreactivity, and a significant correlation was found between GSTP1 expression and regional nodal metastasis of NPC [30]. In tumors with EGFR aberrant activation, GSTP1 was phosphorylated and activated, leading to drug inactivation and drug resistance [31].…”
Section: Discussionmentioning
confidence: 99%
“…One plausible explanation for this observed phenomenon is that the Bcl-2 protein has been implicated as a regulator of transport through the nuclear pore (21). GST-pi, which has a molecular weight of 22 kDa, has the potential to gain entry into the nucleus through the nuclear pore complex (22). The precise role of GST-pi in the nucleus has not been ascertained, although an increased amount of nuclear GST-pi expression has been observed in breast cancer cells resistant to doxorubicin and cis-diamminedichloroplatinum (II; 23).…”
Section: Figurementioning
confidence: 99%